Sufisme-Persia dan Pengaruhnya Terhadap Ekspresi Budaya Islam Nusantara - Fahruddin Faiz (UIN Sunan Kalijaga Yogyakarta, 2016)
There are numerous religious and cultural ethnic groups worldwide, many of which have mutual interactions with each other. For hundreds of years, Persian as well as Shi‘a communities have been known as minority groups with considerable influence on some Eastern and Western societies. The following article try to uncover modes of Indonesian Islamic culture, which have influenced by Persian Sufism, along with its Syi’ah tendencies. The purpose of this essay is to display the influence of Persian Sufism in the cultural expressions of Moslems in Indonesia in early Islam era. With this purpose in mind, a comprehensive bibliography of works published related to the issues is presented. An attempt is also made to present the influence of Persian Sufism figures and elements on the historical and modern Indonesian Islam.[Terdapat beragam kelompok religius dan etnis yang tersebar di berbagai belahan dunia yang memiliki interaksi timbal balik satu sama lain. Selama ratusan tahun, Bangsa Persia, sebagaimana halnya komunitas Syi’ah, telah dikenal sebagai kelompok minoritas yang memiliki pengaruh yang patut diperhitungkan bagi masyarakat dunia, baik di belahan Barat maupun Timur. Artikel berikut ini mencoba untuk mengungkap modus budaya Islam Indonesia yang telah terpengaruh oleh sufisme Persia bersamaan dengan kecenderungan Syi’ah. Tujuan tulisan ini adalah menampilkan pengaruh sufisme Persia dalam ekspresi kultural umat Islam Indonesia di masa awal. Dengan demikian, karya-karya bibliografi komprehensif terkait hal tersebut akan disajikan. Sebuah upaya juga dibuat untuk menyajikan pengaruh dari figur-figur sufi Persia dan beberapa unsur historis dan modern dalam Islam Indonesia.]